Plant Flavonoid Content Modified by Domestication - Urzua-Moll, A (Entomological Society of America, 2017)
Plant domestication can modify and weaken defensive chemical traits, reducing chemical defenses in plants and consequently their resistance against pests. We characterized and quantified the major defensive flavonols and isoflavonoids present in both wild and cultivated murtilla plants (Ugni molinae Turcz), established in a common garden. We examined their effects on the larvae of Chilesia rudis (Butler) (Lepidoptera: Arctiidae). Insect community and diversity indices were also evaluated. We hypothesized that domestication reduces flavonoid contents and modifies C. rudis preference, the insect community, and diversity. Methanolic extracts were obtained from leaves of U. molinae plants and analyzed by high performance liquid chromatography. Results showed higher insect numbers (86.48%) and damage index (1.72±0.16) in cultivated plants. Four new first records of insects were found associated with U. molinae. Diversity indices, such as Simpson, Shannon, and Margalef, were higher in cultivated plants than in wild plants. Furthermore, eight isoflavonoids were identified in U. molinae leaves for the first time. The five flavonols showed higher concentrations in wild U. molinae leaves (89.8 μg/g) than in cultivated plants (75.2 μg/g); however, no differences were found in isoflavonoids between wild and cultivated plants. The larvae of C. rudis consumed more leaf material of cultivated plants than wild plants in choice (3.8 vs. 0.8 mm2) and no-choice (7.5 vs. 3.0 mm2) assays. Our study demonstrates that domestication in U. molinae reduces the amount of flavonoids in leaves, increasing the preference of C. rudis and the insect community. © The Authors 2017.